Innovative research in Clinical Approaches in Health Psychology - Cudris-Torres, Lorena; Bermúdez, Valmore; Gutiérrez García, Raúl A (Gaceta Médica de Caracas, 2021)
The National Academy of Medicine of Venezuela, interested in studying in-depth phenomena that affect the mental health of the human being from a biopsychosocial perspective, took the initiative to publish this supplement of the Gaceta Medica de Caracas dedicated to innovative research in Clinical Psychology and Health. We especially appreciate the invitation of the Board of Directors of the Academy and the Editor-in-Chief, Dr. Manuel Velasco, to prepare this supplement, as well as the great support, received from the Senior Editor, Dr. Anita Stern Israel.